2012
DOI: 10.1590/s1415-43662012001200007
|View full text |Cite
|
Sign up to set email alerts
|

Produção de fitomassa em genótipos de citros submetidos a estresse hídrico na formação do porta-enxerto

Abstract: R ESU M ODevido à importância dos porta-enxertos no sucesso da citricultura e sua influência na tolerância a fatores de estresse, desenvolveu-se este estudo com o objetivo de avaliar a tolerância de porta-enxertos de citros ao estresse hídrico. Estudaram-se dois fatores: manejo hídrico ('sem estresse' e 'com estresse', neste último caso, com irrigação baseada em 50 e 25% da capacidade de campo) e porta-enxerto (10 genótipos de citros fornecidos pelo Programa de Melhoramento Genético de Citros da Embrapa Mandio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
0
4
1
2
Order By: Relevance
“…The same explanation can be attributed to the root / shoot ratio, even if there was no statistical difference a greater increase of the root in relation to the aerial part could be observed, in the attempt to expand its volume in the soil to fetch water and nutrients. Suassuna et al (2012) found increases in the root/ shoot ratio in some citrus genotypes also submitted to water deficiency, differing in this way with the research developed here.…”
Section: Transpirationcontrasting
confidence: 99%
“…The same explanation can be attributed to the root / shoot ratio, even if there was no statistical difference a greater increase of the root in relation to the aerial part could be observed, in the attempt to expand its volume in the soil to fetch water and nutrients. Suassuna et al (2012) found increases in the root/ shoot ratio in some citrus genotypes also submitted to water deficiency, differing in this way with the research developed here.…”
Section: Transpirationcontrasting
confidence: 99%
“…Nas plantas com menores condutâncias, como as enxertadas em MXWL x LHA, pressupõe-se a ocorrência de danos metabólicos (Campos et al, 2011). As médias de condutância determinadas foram semelhantes às relatadas por Suassuna et al (2012) para laranjeiras 'Valência' em deficit hídrico. Magalhães Filho et al (2008) verificaram, em laranjeiras 'Valência' sobre 'Cravo' e trifoliata, condutância estomática próxima à Figura 2.…”
Section: Resultsunclassified
“…If there is no LAI expansion due to water stress, carbon and energy productions are reduced, causing the plants to direct their metabolism to escape measures, that is, Engenharia Agrícola, Jaboticabal, v.39, n.4, p.434-443, jul./aug. 2019 a defense mechanism that distributes assimilates to the underground organs (Suassuna et al, 2012). This impairs plant development and has negative consequences on tuber production, as indicated by the results presented in this study.…”
Section: Resultsmentioning
confidence: 71%